Feasibility and safety of endoscopic resection for duodenal gastrointestinal stromal tumors - Luo, Shao-Bin; Liu, Zu-Qiang; Wang, Li; Zhang, Yi-Qun; Cai, Ming-Yan; Li, Quan-Lin; Zhou, Ping-Hong (Endoscopy International Open, 2025)
Endoscopic resection for duodenal gastrointestinal stromal tumors (GISTs) is still considered a great challenge with a high risk of complications. This study aimed to evaluate effectiveness and safety of endoscopic resection for duodenal GIST.Between June 2013 and August 2024, we performed a retrospective study of patients with duodenal GISTs who underwent endoscopic resection at Zhongshan Hospital. Data on patient characteristics, clinical outcome, and follow-up were collected.A total of 73 patients with duodenal GISTs were enrolled, including 31 patients who underwent endoscopic submucosal dissection (ESD) and 42 who underwent endoscopic full-thickness resection (EFTR). Mean lesion size was 1.2 ± 0.5 cm and 1.9 ± 0.9 cm, respectively. En bloc resection rates were 96.8% and 95.2%, respectively. Rates of R0 resection were 45.2% and 42.9%, respectively. Rates of R1 resection were 54.8% and 57.1%, respectively. No patient transferred to open surgery. Postoperative adverse events included delayed bleeding (1 case), delayed perforation (1 case), delayed wall edema (2 cases), hydrothorax (1 case), and retroperitoneal infection (1 case). Mean hospital stays were 4.1 ± 2.8 days and 6.2 ± 4.9 days, respectively. No metastasis or duodenal stenosis were detected during the follow-up period (64.8 ± 43.6 months and 61.3 ± 40.2 months, respectively). Local recurrence occurred in one patient with high recurrence risk at 56 months after EFTR.ESD and EFTR are safe, minimally invasive treatments for duodenal GISTs. Moreover, the EFTR technique may have advantages of completely resecting lesions originating from the deep muscularis propria layer, particularly lesions with extraluminal growth.
Keywords: Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Polyps / adenomas / ...